The T phase with the V6Si5 type structure in the Mo-Si-Ti system studied by ab initio calculations and X-ray diffraction. (15th January 2019) - Colinet, C.; Joubert, J.-M.; Tedenac, J.-C.
Abstract: Previous experimental studies in the Mo-Si-Ti system have shown the existence of a ternary phase around the composition Mo4 Si9 Ti7 . No crystal structure was indicated for this phase. In the frame of a complete DFT study of phase stability in this system, we have discovered that this compound could have the V6 Si5 -type structure. The synthesis of the compound and the X-ray diffraction analysis using the Rietveld method confirmed the prediction not only of the phase structure but also of the site occupancies. Graphical abstract: Calculated partial isothermal section of the Mo-Si-Ti system at 500 K. Unlabelled Image